SSDStreamer: Specializing I/O Stack for Large-Scale Machine Learning - Bae, J. (IEEE Explore, 2020)
Abstract—This article presents SSDStreamer, an SSD-based caching system for largescale machine learning. By using DRAM as stream buffer, instead of an upper-level cache, SSDStreamer signiﬁcantly outperforms state-of-the-art multilevel caching systems on Apache Spark, while requiring much less DRAM capacity.